2017
DOI: 10.3906/sag-1602-181
|View full text |Cite
|
Sign up to set email alerts
|

Endosonogragphic features of lesions suggesting gastricectopic pancreas: experience of a single tertiary center

Abstract: Background/aim: We aimed to present the endoscopic ultrasound (EUS) features of gastric lesions suggesting gastric ectopic pancreas during upper gastrointestinal endoscopy that were diagnosed in our gastroenterology unit, which is a tertiary center for endoscopic procedures in Turkey. Materials and methods:The data of patients who underwent upper gastrointestinal EUS in our center between April 2012 and July 2014 were retrospectively analyzed.Results: All of the lesions suggesting gastric ectopic pancreas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A characteristic central dimpling of the mucosa, which represents a ductal opening, has been reported in 34%–81% of cases. 12 , 13 EUS is the procedure of choice to evaluate submucosal lesions, and ectopic pancreas should be on the differential diagnosis, particularly if the lesion is in the prepyloric region of the stomach. EUS features include indistinct borders (77%), heterogenous echotexture (88%), and an anechoic duct-like structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A characteristic central dimpling of the mucosa, which represents a ductal opening, has been reported in 34%–81% of cases. 12 , 13 EUS is the procedure of choice to evaluate submucosal lesions, and ectopic pancreas should be on the differential diagnosis, particularly if the lesion is in the prepyloric region of the stomach. EUS features include indistinct borders (77%), heterogenous echotexture (88%), and an anechoic duct-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…EUS features include indistinct borders (77%), heterogenous echotexture (88%), and an anechoic duct-like structure. 12 In a case series of 26 patients, Park et al 13 noted that 76% of gastric ectopic pancreatic lesions involved 2 or more sonographic layers on EUS. The diagnosis of ectopic pancreas often requires endoscopic or surgical resection for histopathologic confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al [25] suggested that it was more di cult to maintain a scope stably in the lower third area of the stomach. In addition, it is known that ectopic pancreas is more frequently detected in the antrum compared with corpus or cardia [26][27][28][29]. Ectopic pancreas is a heterogeneous lesion associated with muscular wall thickening, so it might be di cult to obtain adequate tissue from ectopic pancreas using EUS-FNTA [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is known that ectopic pancreas is more frequently detected in the antrum than it is in the corpus or cardia. [ 26 29 ] Ectopic pancreas is a heterogeneous lesion associated with muscular wall thickening; therefore, it might be difficult to obtain adequate tissue from ectopic pancreas using EUS-FNTA. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation